HUBUNGAN 4 PILAR MANAJEMEN DM DENGAN KADAR GLUKOSA DARAH PASIEN DM TIPE 2 DI WILAYAH KERJA PUSKESMAS KASSI-KASSI KOTA MAKASSAR - erlina yapintowe kongkoli; heriansyah heriansyah; Alfi Syahar Yakub; Sudirman Sudirman (Media Keperawatan:Politeknik Kesehatan Makassar, 2022)
Diabetes Mellitus is a syndrome indicated by the blood glucose raising above the normal level. In order to keep the blood glucose at the safe level, four pillars of DM management are worth implementing. Those pillars include knowledge, dietary habit, physical exercise, and medication adherence to oral hypoglycemic drugs consumption.This study aimed to find out the relation between four pillars of DM management and blood glucose level of type 2 DM patients. This study used quantitative analytics approach with cross-sectional design. This study was held from May to June 2019 at Kassi-Kassi Health Center, Makassar. The population of this study was all 70 type 2 DM patients being under treatment in the health center. Of this population, 35 samples were selected using purposive sampling technique.The analysis found that variables that relate closely to blood glucose level are knowledge (p=0.045), dietary habit (p=0.018), physical exercise (p=0.01), and medication adherence to drugs consumption (p=0.00). In conclusion, knowledge, dietary habit, physical exercise, and medication adherence to drugs consumption relate to glucose blood level.